The Resilience of Healthcare Workers in Hospital During Covid-19 Crisis - Putra, Riyan Sisiawan; Tri Siwi Agustina (Universitas Airlangga, 2024)
The outbreak of the COVID-19 pandemic in all corners of the world has made all activities from various sectors difficult and even experience complete paralysis. As a result of the COVID-19 pandemic, a crisis emerged in various organizations engaged in the medical and non-medical fields. With the crisis due to the COVID-19 pandemic, a transformational leadership role is needed as a form to overcome feelings of worry, fear, and anxiety that arise in healthcare workers. The purpose of this review is to examine the resilience of healthcare workers amid the outbreak of the COVID-19 pandemic. Through well-established adopted questionnaires, data were collected from healthcare workers (N=134) treating COVID-19 patients in the Islamic Hospital in Surabaya, Indonesia. This type of research uses a quantitative approach, a sampling method with census technicalities, and the Partial Least Square (PLS) analysis method. The results showed that transformational Leadership had a positive effect on health workers. Then, there was no significant influence of transformational Leadership on negative effects on health workers. At the same time, from positive effects, it was found to have a significant influence on the resilience of health workers of Islamic Hospital during the COVID-19 crisis.